PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN, CITRA MEREK DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN JASA ASURANSI JIWA (Studi Pada AJB Bumiputera 1912 Cabang Cibinong) - Adiputra, Yustinus Riyan; Khasanah, Imroatul (Diponegoro Journal of Management, 2016)
This study aims to determine the effect of product quality, service quality, brand image and perception of price on purchase decisions of insurance services at AJB Bumiputera 1912 and analyze the most dominant factor in influencing the purchasing decisions of insurance services at AJB Bumiputera 1912.This research was conducted at AJB Bumiputera 1912 branch offices Cibinong. Methods of data collection in this study is a questionnaire filled out by the respondents AJB Bumiputera 1912 Cibinong customers who have made purchases insurance premiums, samples were taken of 100 respondents. The sampling technique in this research is non probability sampling with purposive sampling method. The analysis used in this study include the analysis of index numbers, validity, reliability test, classic assumption test, multiple linear analysis and hypothesis testing that includes t-test, F, and the coefficient of determination ( ).Regression test results showed that the variable product quality, service quality, brand image and perception of price positive influence on purchase decisions of insurance services AJB Bumiputera 1912. Variable service quality has the greatest influence in the amount of 0.327%. Adjust R Square Results showed that 73.1% of purchase decisions variation can be explained by four independent variables in the regression equation, while the remaining 26.9% is explained by other variable not include in this study.